Mapping Tsunami Disaster Evacuation Routes Based on Geographic Information Systems (Case Study: Tambakrejo Village, Malang Regency, East Java) - Dalendra Kardina; Adi Susilo; Fadly Usman (Postgraduate, University of Mataram, 2025)
Indonesia is situated amidst three major tectonic plates: the Indo-Australian Plate, Eurasian Plate, and Pacific Plate. As a consequence, the country is characterized by numerous volcanoes, frequent earthquakes in various regions, and the occurrence of tsunamis. Particularly in the southern region of Java Island, this coastal area is a disaster-prone area. One of the areas is Tambakrejo Village, which is located in the coastal area of Malang Regency, which has potential in the form of beautiful beaches, abundant fishery products and development of the tourist village. This research aims to create a tsunami evacuation route map using a GIS. The digital elevation model data was obtained from Geospatial Information Agency using reclassification based on variations in altitude levels. Distance data from the coastline is processed using a base map of the research location and assisted by the Multiple Ring Buffer Toolbox. Land use data is processed using the Maximum Likelihood Classification process, the data used is Landsat 8 imagery. Determination of tsunami evacuation routes is carried out by implementing the Network Analyst method. The Network Analyst method uses the starting point of the incident to the end point of the facility to produce an appropriate evacuation route. The results show four new gathering points and 6 recommended evacuation routes for Sendangbiru, Tamban and Sendiki Beaches respectively.